A Study on the Relationship between Minimum Wage and Income Rise on Economic Growth in Nigeria - Abere, Dr. Benjamin Olusola; Igbafe, Dr. Okhai (Direct Research Journal of Management and Strategic Studies, 2023)
Minimum wages and income rise are capable of improving the living standards of laborers, especially the poor. This paper examines the effects of minimum wage and income rise on economic growth in Nigeria. To achieve this task a model of investment was specified explaining minimum wage, Interest Rate, Credit to Private Sector and Inflation Rate in Nigeria. Johansen co-integration was used to analyze both short and long run relationship between variables. Research findings reveal that there is an inverse relationship between Investment (INV), interest rate INT and credit to private sector CPS in the long run while minimum wage MWG and inflation rate INF are having a direct relationship with investment in the long run. The long-run result conforms to the a priori expectation of inverse relationship between Investment (INV), interest rate INT and credit to private sector CPS in the long run. Based on our findings this work therefore recommends that; there is need for stakeholders, particularly the labor union organizations to have severally called for wage indexation in Nigeria. The minimum wage is required to ensure the basic needs of the laborers and dependents in their family. Economic growth and price inflation require the adjustment of minimum wages. Therefore, government must be ready to adjust the minimum wage when there is a change in prices of commodities and services. Government on their part should ensure that her economic policies are geared toward development  of  a  good  industrial  climate  and  environment  that  encourages  industrial harmony, and which will also boost organizational and national development.  Workers should therefore develop themselves to acquire more relevant skills and competencies in order to avoid becoming skill obsolete and possible redundancy in order to remain relevant in existing and emerging industrial relations trends and issues.
Keywords: Minimum wage; income rise; credit to private sector; inflation